A better understanding of loss prevention in the maritime industry – a case study in best practices - Swenzen, Eric (My University, 2026)
Maritime accidents cause significant human, economic and environmental losses, and there is a large societal need to minimize the accidents and claims. 2,646 accidents were reported on average annually between 2014 and 2022. Loss prevention is characterised by the analysis of past claims, inspections and general advice for Protection & Indemnity (P&I) Club members. The project was conducted by collecting qualitative data from key onshore management personnel at shipping companies, with no or few claims. These companies were selected by the insurance company The Swedish Club. The results and the analysis are presented in this thesis. The research is limited to data collected from six companies. The information was gathered from relevant sources of academic literature and partly from semi-structured interviews. Loss prevention practices are limited to the participating companies. Data collected shows that the human factor is causing most of the maritime accidents, directly or indirectly. The primary research shows that a successful corporate culture, which involves the crew in all aspects of designing, equipping, training and auditing, helps to keep accidents at a minimum. This includes a friendly, open and non-blame corporate culture, where all suggestions and opinions are considered.
Keywords: Loss prevention; accidents; claims; marine insurance; policy; hull & machinery; H&M; protection & indemnity; P&I; human factor